Moral Hazard in Ancillary Private Health Insurance in Australia - Nguyen, Lan; Worthington, Andrew C (My University, 2021)
We assess moral hazard in Australian ancillary or extras (nonhospital) private health insurance (PHI) relating to dental care services using the longitudinal data in the Household, Income and Labour Dynamics in Australia (HILDA) Survey. Cross-sectional probit regressions specify dental care (the most important expenditure component of ancillary cover) as a function of endogenous PHI policy holding, self-assessed health condition, health risk factors and socioeconomic controls including age, income, education, family structure and welfare status. We find that moral hazard is present resulting in the possible overuse of dental care services by PHI holders, bearing in mind this is overuse in relative rather than absolute terms. However, we also find using dynamic analysis that while there is no evidence of pent-up demand (previously uninsured policyholders accessing more dental care services initially) any sort of PHI holding, however sporadic, is always associated with significantly more likely use of dental care services than persons that have never held PHI. This supports the role of PHI in fostering good health care behavior and possibly countering ex ante moral hazard.
SSRN
Keywords: Health and wellbeing